Protective Role of Kynurenine 3-Monooxygenase in Allograft Rejection and Tubular Injury in Kidney Transplantation - Lassiter, Randi; Merchen, Todd D.; Fang, Xuexiu; Wang, Youli (Frontiers in Immunology, 2021)
Renal tubular epithelial cells (TEC) are the primary targets from ischemia-reperfusion injury (IRI) and rejection of recipient’s immune response in kidney transplantation (KTx). However, the molecular mechanism of rejection and IRI remains to be identified. Our previous study demonstrated that kynurenine 3-monooxygenase (KMO) and kynureninase are reduced in ischemia-reperfusion procedure and further decreased in rejecting allograft among mismatched pig KTx. Herein, we reveal that TEC injury in acutely rejecting allografts is associated with alterations of Bcl2 family proteins, reduction of tight junction protein 1 (TJP1) and TEC-specific KMO. Three cytokines, IFNγ, TNFα, and IL1β, reported in our previous investigation are identified as triggers of TEC injury by altering the expression of Bcl2, BID and TJP1. Allograft rejection and TEC injury are always associated with a dramatic reduction of KMO. 3HK and 3HAA, as direct and downstream products of KMO, effectively protect TEC injury via increasing BcL-xL and TJP1. Both 3HK and 3HAA further prevent allograft rejection by inhibiting T cell proliferation and upregulating aryl hydrocarbon receptor expression. Pig KTx with administration of DNA nanoparticles (DNP) which induce expression of indoleamine 2,3-dioxygenase (IDO) and KMO to increase 3HK/3HAA showed an improvement of allograft rejection, and murine skin transplant in IDO knockout mice with injection of 3HK have shown improvement of allograft rejection. Taken together, our data provided strong evidence that reduction of KMO in graft is the main mediator to result in allograft rejection and loss, prevention of KMO decrease can effectively improve allograft outcome by attenuating allograft rejection and maintaining graft barrier function.